Tracking five years of teacher education enrolment at a South African university: Implications for teacher education - Davids, N.; Waghid, Y. (South African Journal of Higher Education, 2020)
The faculty in which we are based offers two initial teacher training programmes: the Postgraduate Certificate in Education (PGCE); and the four-year BEd qualification ‒ allowing students to pursue a specialisation in either the foundation or intermediate phase. Compared to other faculties, the Faculty of Education occupies the somewhat precarious label of being one of the “most transformed” faculty in the university. In other words, given the historical privilege of the university, the Faculty of Education is considered to have shown the most evident strides towards transformation in terms of racial representation. A cursory glance at statistics of student enrolments over a five-year period, provides interesting insights ‒ insights, which, as we shall discuss in this article, should be interpreted with great caution. The interest and purpose of this article is to use the student enrolment statistics at a historically advantaged university as one indicator of a representative sample of teachers, who are likely to enter South African schools. The interest, on the one hand, is to gain an idea of the corpus of enrolled student teachers ‒ by taking account of race and gender. On the other hand, we intend to use this data to further our discussions on representation, and the implications for teacher education, and hence, teaching. In the background, are inevitable concerns centring on notions of representation in relation to conceptions of transformation.